2021
DOI: 10.7326/m20-7725
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for COVID-19 Vaccination: A Call to Action for Clinicians on Immunization Information Systems

Abstract: Immunization information systems (IISs) play a central role in coordinating distribution, administration, documentation, and monitoring of COVID-19 vaccination. In this commentary, the authors provide an introduction to IISs and discuss how clinicians can help maximize their utility in the COVID-19 pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Strengthening IISs had been a core goal of COVID-19 vaccine implementation plans [18] . Limited initial COVID-19 vaccine supply combined with tiered rollout of vaccines to priority groups and the need for timely administration of a second dose led to substantial investments in U.S. immunization infrastructure to monitor COVID-19 vaccine distribution and coverage in near real-time [19] , [20] . Because the federal government procured all COVID-19 vaccines used in the U.S., the federal government was also able to mandate that vaccination providers report administration of COVID-19 vaccine to IISs within 24–72 hours as part of the COVID-19 vaccine provider enrollment agreement, which led to substantial improvements in IIS data quality for COVID-19 vaccination [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Strengthening IISs had been a core goal of COVID-19 vaccine implementation plans [18] . Limited initial COVID-19 vaccine supply combined with tiered rollout of vaccines to priority groups and the need for timely administration of a second dose led to substantial investments in U.S. immunization infrastructure to monitor COVID-19 vaccine distribution and coverage in near real-time [19] , [20] . Because the federal government procured all COVID-19 vaccines used in the U.S., the federal government was also able to mandate that vaccination providers report administration of COVID-19 vaccine to IISs within 24–72 hours as part of the COVID-19 vaccine provider enrollment agreement, which led to substantial improvements in IIS data quality for COVID-19 vaccination [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that including data from IIS can increase appropriate administration of vaccines, [23] , [24] , [25] by providing historical records of vaccination, thereby reducing misclassification of vaccination status. [13] , [14] , [15] These studies suggest that strengthening links between EHR and IIS are critical to improve the ability to conduct research related to vaccination status [26] and reinforce the need for integration of IIS data into EHR systems for timely and unbiased evaluations of vaccine safety. As described by McCarthy et al, the addition of IIS data can improve the accuracy of analyses conducted by the VSD.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Providers are required to document all COVID-19 vaccination within 24–72 h of administration; many states are facilitating this process through their existing IIS. [15] …”
Section: Introductionmentioning
confidence: 99%